Integrative men's health - Spar, Myles D.; Muñoz, George E. (Weil integrative medicine library., 2014)
"As a field, men's health is far behind women's health in terms of the availability of reliable, scientifically based information that men, their partners, and health care providers can rely on when seeking information and treatment. Moreover, integrative approaches are becoming more popular with men whose healthcare providers understand that most of the leading causes of morbidity and mortality in men, including cardiovascular disease, cancer, urologic disease, and sexual dysfunction, can be ameliorated using an integrative approach, with more emphasis on the patient-provider relationship, lifestyle change, and the use of proven complementary modalities. Integrative Men's Health provides an evidence-based perspective on the health problems that affect men and the ways in which such problems may be prevented or treated utilizing a broad armamentarium of approaches - from conventional tools to complementary modalities. All chapters take into consideration of all the factors that influence men's health including body, mind, and spirit in a way that neither rejects alternative approaches nor accepts any of them uncritically"--Publisher's description